2021
DOI: 10.3389/fsurg.2021.693562
|View full text |Cite
|
Sign up to set email alerts
|

An Initial 5-Year Single-Center Experience of 365 Patients Undergoing the Video-Assisted Thoracoscopic Surgery for Nuss Procedure for Pectus Excavatum in Resource-Scare Setting

Abstract: Background: Little is known about video-assisted thoracoscopic surgery in the Nuss procedure (VATS-NUSS) and its postoperative outcomes in the resource-scarce conditions in clinical practice such as Vietnam. Available evidence in the literature was mostly reported from large institutions in developed countries. Hence, this study was conducted to review our initial large single-center experience in the use of the VATS-NUSS for patients with pectus excavatum (PE) within 5 years.Methods: Data from 365 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Furthermore, a common complication was pleural effusion (10.34% in Maribor and 4.76% in Novi Sad). The total of 8% of patients with pleural effusions reported in our study is in accordance with the literature findings (up to 10%) [26,29,30]. Unlike as expected, we noted less pleural effusions after the standard Nuss procedure compared to the extrapleural thoracoscopic modification.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, a common complication was pleural effusion (10.34% in Maribor and 4.76% in Novi Sad). The total of 8% of patients with pleural effusions reported in our study is in accordance with the literature findings (up to 10%) [26,29,30]. Unlike as expected, we noted less pleural effusions after the standard Nuss procedure compared to the extrapleural thoracoscopic modification.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed no statistically significant difference (p = 0.94) in the outcomes and complication rates between these two procedures (standard and thoracoscopic extrapleural modification of the Nuss procedure), which implies that both procedures can be used as they are safe and effective. Despite all the innovations and modifications of Nuss procedure, we are still facing similar levels of complications worldwide [22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%